Palms predict the distributions of birds in southwestern Amazonia and are potential surrogates for land-use planning by citizen scientists - Menger, Juliana; Santorelli Junior, Sergio; Emilio, Thaise [UNESP]; Magnusson, William E.; Anciães, Marina (Springer Nature, 2024)
In the absence of high-quality biodiversity data, land-use planners and conservationists often rely on biodiversity surrogates. Many studies have proposed surrogates based on assumptions about the environmental niches of species. However, the use of such assumptions is not always useful because biological processes and ecological interactions can operate at different scales due to the non-uniform geographical distribution of environmental conditions. In such cases, compositional heterogeneity across the same region can be expected but is often hidden by broad-scale environmental data. Furthermore, these assumptions may obscure important relationships between species and their environment. To elucidate this issue, we asked whether biotic interactions between two taxonomic groups are more important than other factors in reflecting the distribution of unsampled species. To do this, we compared the relationship between the distribution of bird species and the distribution of the five most-abundant palm species which are often considered indicators of bird communities. These species include Lepidocaryum tenue, Oenocarpus bataua, Oenocarpus bacaba, Mauritiella aculeata, and Attalea speciosa. Additionally, we considered environmental factors (precipitation, water-table levels, sand and clay contents) and the ecoregions along the Purus-Madeira interfluve as drivers of bird species composition. Our results show that bird-assemblage composition was strongly correlated with changes in palm-species abundance. The presence-absence data for bird-species showed that palm-species alone explained 25% and 19% of composition of all birds and only canopy birds, respectively. These palm species are abundant and can be easily identified and monitored by non-specialists, such as citizen scientists. Citizens are often involved in data acquisition but may not have the experience to sample large assemblages consisting of hundreds of species; thus, these five most-abundant palms species could serve as a cost-effective and efficient biodiversity surrogate for birds.
Keywords: Biodiversity surrogates; Biotic interaction; Compositional heterogeneity; Conservation planning; Local communities